Classification of Vitamin D status based on Vitamin D metabolism: a randomized controlled trial in hypertensive patients - Zelzer, Sieglinde; Meinitzer, Andreas; Enko, Dietmar; Keppel, Martin H.; Herrmann, Markus; Theiler-Schwetz, Verena; Trummer, Christian; Schmitt, Lisa; Tomaschitz, Andreas; Sadoghi, Patrick; Dierkes, Jutta; Pludowski, Pawel; et al. (Nutrients, 2024)
Circulating 25-hydroxyvitamin D (25(OH)D) is the generally accepted indicator of vitamin D status. Since hydroxylation of 25(OH)D to 24-25-dihydroxyvitamin D (24,25(OH)2D) is the first step of its catabolism, it has been suggested that a low 24,25(OH)D level and a low vitamin D metabolite ratio (VMR), i.e., 24,25(OH)2D divided by 25(OH)D, may indicate high vitamin D requirements and provide additional diagnostic information beyond serum 25(OH)D. We, therefore, evaluated whether the classification of “functional vitamin D deficiency”, i.e., 25(OH)D below 50 nmol/L, 24,25(OH)2D below 3 nmol/L and a VMR of less than 4%, identifies individuals who benefit from vitamin D supplementation. In participants of the Styrian Vitamin D Hypertension trial, a randomized controlled trial (RCT) in 200 hypertensive patients with serum 25(OH)D below 75 nmol/L, who received either 2.800 international units of vitamin D per day or placebo over 8 weeks, 51 participants had functional vitamin D deficiency. In these individuals, there was no treatment effect of vitamin D supplementation on various parameters of bone metabolism and cardiovascular risk except for a significant effect on parathyroid hormone (PTH) and expected changes in vitamin D metabolites. In conclusion, a low vitamin D metabolite profile did not identify individuals who significantly benefit from vitamin D supplementation with regard to bone markers and cardiovascular risk factors. The clinical significance of functional vitamin D deficiency requires further evaluation in large vitamin D RCTs.